2018
DOI: 10.1007/s00411-018-0742-9
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in histone acetylation following exposure to 60Co γ-rays and their relationship with chromosome damage in human lymphoblastoid cells

Abstract: Chromosome damage is related to DNA damage and erroneous repair. It can cause cell dysfunction and ultimately induce carcinogenesis. Histone acetylation is crucial for regulating chromatin structure and DNA damage repair. Ionizing radiation (IR) can alter histone acetylation. However, variations in histone acetylation in response to IR exposure and the relationship between histone acetylation and IR-induced chromosome damage remains unclear. Hence, this study investigated the variation in the total acetylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In previous studies of my group, exposure of fruit flies to 2G (GSM) mobile phone EMFs induced extensive DNA damage in the gametes leading to cell death and reproductive decline (Panagopoulos et al 2007Chavdoula et al 2010;Panagopoulos 2012). Since DNA damage is converted into chromosomal damage during the early M phase of the cell division cycle (Terzoudi and Pantelias 2006;Pantelias and Terzoudi 2010;Terzoudi et al 2011;Tian et al 2018), the recorded chromosomal damage induced by the UMTS (3G/4G) MT/WC EMF and/or caffeine and/or gamma radiation, is evidently due to DNA damage caused by these stressors.…”
Section: Discussionmentioning
confidence: 97%
“…In previous studies of my group, exposure of fruit flies to 2G (GSM) mobile phone EMFs induced extensive DNA damage in the gametes leading to cell death and reproductive decline (Panagopoulos et al 2007Chavdoula et al 2010;Panagopoulos 2012). Since DNA damage is converted into chromosomal damage during the early M phase of the cell division cycle (Terzoudi and Pantelias 2006;Pantelias and Terzoudi 2010;Terzoudi et al 2011;Tian et al 2018), the recorded chromosomal damage induced by the UMTS (3G/4G) MT/WC EMF and/or caffeine and/or gamma radiation, is evidently due to DNA damage caused by these stressors.…”
Section: Discussionmentioning
confidence: 97%
“…Studies have shown that relative levels of histone acetylation and deacetylation are of significance for the regulation of pathophysiological processes, including proliferation, cell-cycle progression, differentiation, immune evasion, inflammatory lesion, apoptosis and death (143)(144)(145). Pharmacological inhibition of HdAc activity or expression alters chromatin acetylation levels, subsequently confusing boundaries between transcriptionally active and quiescent chromatin (146)(147)(148).…”
Section: Discussionmentioning
confidence: 99%
“…(Panagopoulos et al 2007Chavdoula et al 2010;Panagopoulos 2012). Since DNA damage is converted into chromosomal damage during the early M phase of the cell division cycle (Terzoudi and Pantelias 2006;Pantelias and Terzoudi 2010;Terzoudi et al 2011;Tian et al 2018), the recorded chromosomal damage induced by the UMTS (3G) MT EMF and/or caffeine is apparently due to DNA damage caused by these stressors. The DNA damage recorded in our previous studies was induced only by a few min daily exposures for a few days for radiation intensities down to 1 μW/cm 2 .…”
Section: Discussionmentioning
confidence: 99%